ANALYSIS OF MARKETING COMMUNICATION AND ITS EFFECT ON CONSUMER PURCHASE INTENTION OF GOLD METAL AT PT. PEGADAIAN (PERSERO) MANADO UTARA BRANCH - Ering, Merry Christy; Pandowo, Merinda (FEB Universitas Sam Ratulangi Manado, 2015)
Marketing Communication becomes increasingly necessary in today?s competitive environment. In their effort to introduce a product to public, company should provide trusted information about the product so it can attract public attention. Marketing communication becomes important for PT. Pegadaian (Persero) Manado Utara Branch to think seriously about how they can compete effectively with other financial institutions that provide gold metal product. This research is using associative method with multiple regression analysis technique. Questionnaires are distributed to 100 respondents who are the consumers on gold metal. This study found that marketing communication influence on consumer purchase intention simultaneously, while advertising has negative significant and other variables positively significant influence on consumer purchase intention partially, where personal selling is the most dominant variable. Author has recommended that the head of PT. Pegadaian (Persero) Manado Utara Branch need to extensively and widely advertise the gold metal?s information through prints media and electronics, because the more people watch, listen, and read the advertisement, the more it will increase consumer purchase intention. Keywords: marketing communication, advertising, sales promotion, consumer purchase intention.